Perancangan Sistem Informasi Ulangan Online Berbasis Website Pada SMK YP Mulia Jakarta - Hadi Agustiana, Akbar; Ester, Ria; Tri Sundari, Anggita (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
SMK YP Mulia Jakarta is a vocational high school that has adopted technology in its educational process, including the implementation of daily assessments, which were previously managed through Google Forms. Despite its use, this platform has several shortcomings, such as rigid scheduling options, the absence of automatic question randomization, limited participant authentication capabilities, and a lack of automated result analysis. Moreover, since Google Forms is a third-party tool, the school lacks full authority over the system and its data. To overcome these challenges, the author developed a custom web-based online testing system specifically designed to meet the requirements of SMK YP Mulia Jakarta. The system offers features such as configurable test timing, randomized questions, token-based access management, secure user authentication, and real-time, integrated result reporting.